2021
DOI: 10.3390/electronics10131604
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fiber Sensor for PVC Sheet Piles Monitoring

Abstract: This paper examined the impact of optical fiber sensor design, and its integration to PVC (polyvinyl chloride) sheet piles, on deflection and strain monitoring. Optical fiber sensors based on Brillouin light backscattering (BLS) were prepared, as they can provide accurate strain and deflection measurement results. However, depending on the application of sheet piles systems, high deformation of PVC elements can be observed. Therefore, a fiber sensor design is not trivial. Three types of optical fiber coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The material parameters of plain knitted cotton fabric are shown in Table 2. [20,21], organic glass [18,22], three-type polypropylene pipe (PPR pipe) [23], PVC pipe [24], and others. Previous studies [25] have indicated that PVC pipe is a favorable choice for model test pile materials due to its high strength, ease of processing, and other advantages.…”
Section: Reinforcement Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material parameters of plain knitted cotton fabric are shown in Table 2. [20,21], organic glass [18,22], three-type polypropylene pipe (PPR pipe) [23], PVC pipe [24], and others. Previous studies [25] have indicated that PVC pipe is a favorable choice for model test pile materials due to its high strength, ease of processing, and other advantages.…”
Section: Reinforcement Materialsmentioning
confidence: 99%
“…Considering the specific characteristics of this experiment, PVC pipe was selected as the material for the model test pile. The material parameters for the pile are detailed in Table 3, based on research on PVC pipe material properties [24]. To simulate the frictional resistance on the surface of the original pile, the model pile surface is coated with a mixture of poly-amide resin and epoxy resin, onto which sieved medium-coarse sand was applied.…”
Section: Reinforcement Materialsmentioning
confidence: 99%